The deciduous dentition of Homo naledi: A comparative study. Issue 136 (November 2019) - Bailey, Shara E.; Brophy, Juliet K.; Moggi-Cecchi, Jacopo; Delezene, Lucas K.
Abstract: In 2013, 2014 new hominin remains were uncovered in the Dinaledi chamber of the Rising Star cave system in South Africa. In 2015 Berger and colleagues identified these remains as belonging to a new species Homo naledi (Berger et al., 2015). Subsequent comparative studies of the skull, postcrania and permanent dentition have supported this taxonomic affiliation (Harcourt-Smith et al., 2015; Kivell et al., 2015; Irish et al., 2018). The deciduous teeth can offer unique insights into hominin evolution. Due to their early onset and rapid development their morphology is thought to be under stronger genetic control and less influenced by environment than are the permanent teeth. In this study we compared the H. naledi deciduous teeth from the 2013–2014 excavations to samples representing much of the hominin clade including Australopithecus afarensis, Australopithecus africanus, Paranthropus boisei, Paranthropus robustus, early Homo, Homo antecessor, Homo erectus s.l., Homo floresiensis, Middle Pleistocene Homo, Homo neanderthalensis, early Homo sapiens and recent H. sapiens from Sub-Saharan Africa. By making such a broad morphological comparison, we aimed to contextualize the Dinaledi hominins and to further assess the validity of their taxonomic assignment. Our analysis of the deciduous teeth revealed a unique combination of features that mirror (but also expand) that found in the permanent teeth. This mosaic includes an asymmetrical lower canine with a distal tubercle, an upper first molar with a large hypocone and epicrista associated with a mesial cuspule, a molarized lower first molar resembling Paranthropus, and upper and lower second molars that resemble later Homo in their lack of accessory cusps. The unique combination of deciduous dental characters supports previous studies assigning H. naledi to a new species, although its phylogenetic position vis-à-vis other Homo species remains ambiguous.